1991
DOI: 10.1038/352340a0
|View full text |Cite|
|
Sign up to set email alerts
|

Homozygous prion protein genotype predisposes to sporadic Creutzfeldt–Jakob disease

Abstract: The human prion diseases, Creutzfeldt-Jakob disease (CJD) and Gerstmann-Sträussler syndrome (GSS), are neurodegenerative diseases that are unique in being both infectious and genetic. Transmission of both diseases and the animal spongiform encephalopathies (for example, scrapie and bovine spongiform encephalopathy) to experimental animals by intracerebral inoculation with brain homogenates is well documented. Despite their experimental transmissibility, missense and insertional mutations in the prion protein g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
438
3
14

Year Published

1993
1993
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 803 publications
(476 citation statements)
references
References 19 publications
16
438
3
14
Order By: Relevance
“…Interpretation has been hampered by the inability to do confirmatory immunoblotting of formalin-fixed tissue and by the fact that two of the three positive specimens that could be analysed were from individuals with a PRNP codon 129 valine homozygous genotype [50]. Polymorphism at residue 129 of human PrP [encoding either methionine (M) or valine (V)] powerfully affects susceptibility to human prion diseases, with residue 129 acting to restrict the propagation of particular prion strains through conformational selection [6,51,52] and heterozygosity conferring resistance by inhibiting homologous protein-protein interactions [52][53][54]. To date, all patients with neuropathologically confirmed vCJD have been PRNP codon 129 methionine homozygotes [7,26] and have a remarkably uniform and distinct neuropathological phenotype defined by the presence of abundant florid PrP plaques [1] and the propagation of type 4 PrP Sc [2,55] in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation has been hampered by the inability to do confirmatory immunoblotting of formalin-fixed tissue and by the fact that two of the three positive specimens that could be analysed were from individuals with a PRNP codon 129 valine homozygous genotype [50]. Polymorphism at residue 129 of human PrP [encoding either methionine (M) or valine (V)] powerfully affects susceptibility to human prion diseases, with residue 129 acting to restrict the propagation of particular prion strains through conformational selection [6,51,52] and heterozygosity conferring resistance by inhibiting homologous protein-protein interactions [52][53][54]. To date, all patients with neuropathologically confirmed vCJD have been PRNP codon 129 methionine homozygotes [7,26] and have a remarkably uniform and distinct neuropathological phenotype defined by the presence of abundant florid PrP plaques [1] and the propagation of type 4 PrP Sc [2,55] in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Two predominant PrP sc types have been identified, based on the gel mobility of the PrP sc fragments resistant to proteinase K (PK) treatment, and they are associated with different CJD phenotypes (Cali et al, 2006;Gambetti et al, 2003;Monari et al, 1994;Petersen et al, 1994). Parallel to this, PRNP polymorphism at codon 129 (Met 129 →Val) modulates sensitivity to CJD, and methionine homozygosis is a risk factor for sporadic and variant CJD (Collinge, 1999;Ladogana et al, 2005;Palmer et al, 1991). However, conflicting results have been reported about the relationship between polymorphism at codon 129 and the pathological and clinical features of AD (Hooper and Turner, 2008;Poleggi et al, 2008) for reviews) although a systematic meta-analysis of AD genetic association studies revealed PRNP as a susceptible gene ((Bertram and Tanzi, 2008) for review).…”
Section: Introductionmentioning
confidence: 99%
“…Ein Einfluss des Genotyps am Codon 129 des PRNP auf die Suszeptibilität und Inkubationszeit der sCJK ist beschrieben (Palmer et al 1991). Bei CJK-Patienten, deren Erkrankung auf infektiöse menschliche Wachstumshormone (hGH) zurück-zuführen ist, wurden signifikant kürzere Inkubationszeiten bei Homozygotie als bei Heterozygotie am Codon 129 festgestellt (Aignaux et al 1999, Brandel et al 2003.…”
Section: Einflüsse Des Codon-129-genotypsunclassified